Artificial Skin INTEGRA Use in the Treatment of Large Melanocytic Nevi - Geležauskas, Dainius; Dubosaitė, Rūta (Lietuvos chirurgija, 2020)
Melanocytic nevi are congenital, benign, pigmented proliferations. They have high risk of malignancy, most frequently transform to malignant skin melanoma and 70% it occurs in the first life decade. The risk of malignant transformation increases proportionately to their size. The best way to avoid those risks is early and radical excision. In 1996 on the market appeared the Integra™ artificial skin, has made it possible to improve the methods for the elimination of large congenital nevi and significantly reduce the risk of malignant melanoma, at an early age.2011–2019, in Children’s Hospital, Affiliate of Vilnius University Hospital Santaros Clinics, the Integra™ was used to treat congenital melanocytic nevi in four children. Implantation of the skin substitute Integra™ has been successful for all the patients, the prognosis was good.The treatment of congenital melanocytic nevi is a necessity to avoid the risk of developing malignant melanoma. The rarity of this condition has led to the fact that so far there is no universal approach for all the cases. Integra™ artificial skin is an excellent choice for the treatment of congenital melanocytic nevi, especially for paediatric patients.
Keywords: Integra™; artificial skin; skin substitute; congenital melanocytic nevi; malignant melanoma